Towards an on-chip optical microsystem for spectroscopic detection of gastrointestinal dysplasia - Pimenta, Sara Filomena Ribeiro (2019)
This paper presents a CMOS optical microsystem with a 4×4 photodiodes array and their readout electronics, based on 16 light-to-frequency converters, and 16 high selective optical filters, for spectrophotometric measurement of diffuse reflectance and fluorescence signals, applied to the detection of gastrointestinal dysplasia. The photodiodes array is based on n+/p epilayer junction silicon photodiodes. Their readout electronics outputs a digital signal, with a frequency proportional to the photodiode current, featuring a sensitivity of 26 Hz/nA at 550 nm, a spectral resolution of 9 MHz and a power consumption of 1 mW. The optical filters are based on 16 thin film narrow-band Fabry Perot resonators, in which dielectric mirrors are used. They feature high transmittances and low full width half maximum. Experimental measurements, using phantoms representative of the main absorbing, scattering and fluorescence properties of gastrointestinal tissues, proved the viability of the CMOS optical microsystem with the optical filters to extract those signals, when comparing the obtained results with commercial equipment. The implemented apparatus is ready to be used as a portable system on a surgery room to verify the total removing of gastrointestinal cancer tissue. Moreover, the developed approach is a step forward in the implementation of a gastrointestinal dysplasia detection miniaturized tool.